Facile one-step microwave-assisted route towards Ni nanospheres/reduced graphene oxide hybrids for non-enzymatic glucose sensing - Wang, Zhigang (2014)
In this work, a facile one-step microwave-assisted method for deposition of monodisperse Ni nanospheres on reduced graphene oxide (rGO) sheets to form Ni-rGO nanohybrids is discussed. In the presence of hydrazine monohydrate, Ni nanospheres are grown onto rGO sheets using nickel precursor and GO as starting materials in ethylene glycol (EG) solution under a low level of microwave irradiation (300 W) for 20 min, during which GO is also reduced to rGO. The as-prepared nanohybrids exhibit well-dispersed Ni nanosphere (about 80 nm in diameter) loadings and effective reduction of graphene oxide. The resulting Ni-rGO nanohybrids-modified glassy carbon electrode (GCE) shows significantly improved electrochemical performance in nonenzymatic amperometric glucose detection. In addition, interference from the oxidation of common interfering species under physiological conditions, such as ascorbic acid (AA) and uric acid (UA), is effectively avoided.